DNA preserved in jetsam whale ambergris. (26th February 2020) - Macleod, Ruairidh; Sinding, Mikkel-Holger S.; Olsen, Morten Tange; Collins, Matthew J.; Rowland, Steven J.
Abstract : Jetsam ambergris, found on beaches worldwide, has always been assumed to originate as a natural product of sperm whales (Physeteroidea). However, only indirect evidence has ever been produced for this, such as the presence of whale prey remains in ambergris. Here, we extracted and analysed DNA sequences from jetsam ambergris from beaches in New Zealand and Sri Lanka, and sequences from ambergris of a sperm whale beached in The Netherlands. The lipid-rich composition of ambergris facilitated high preservation-quality of endogenous DNA, upon which we performed shotgun Illumina sequencing. Alignment of mitochondrial and nuclear genome sequences with open-access reference data for multiple whale species confirms that all three jetsam samples derived originally from sperm whales ( Physeter macrocephalus ). Shotgun sequencing here also provides implications for metagenomic insights into ambergris-preserved DNA. These results demonstrate significant implications for elucidating the origins of jetsam ambergris as a prized natural product, and also for the understanding of sperm whale metabolism and diet, and the ecological mechanisms underlying these coproliths.